2018
DOI: 10.3390/w10030324
|View full text |Cite
|
Sign up to set email alerts
|

Treatability of a Highly-Impaired, Saline Surface Water for Potential Urban Water Use

Abstract: As freshwater sources of drinking water become limited, cities and urban areas must consider higher-salinity waters as potential sources of drinking water. The Salton Sea in the Imperial Valley of California has a very high salinity (43 ppt), total dissolved solids (70,000 mg/L), and color (1440 CU). Future wetlands and habitat restoration will have significant ecological benefits, but salinity levels will remain elevated. High salinity eutrophic waters, such as the Salton Sea, are difficult to treat, yet more… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…On day 26, when the turbidity of the raw water was 12.5 NTU, the water after cartridge filtration presented 1.13 NTU of turbidity. Pontius [34] showed effective turbidity removal with filters which had smaller size openings, such as 0.45 µm and 0.10 µm. Afkhami et al [12] showed high removal of turbidity with pleated cartridge filters, however they adopted a pressure drop in the system limited to 1 bar and water treatment with artificial turbidity, caused by the addition of kaolinite.…”
Section: Water Quality Parameter Evaluationmentioning
confidence: 99%
“…On day 26, when the turbidity of the raw water was 12.5 NTU, the water after cartridge filtration presented 1.13 NTU of turbidity. Pontius [34] showed effective turbidity removal with filters which had smaller size openings, such as 0.45 µm and 0.10 µm. Afkhami et al [12] showed high removal of turbidity with pleated cartridge filters, however they adopted a pressure drop in the system limited to 1 bar and water treatment with artificial turbidity, caused by the addition of kaolinite.…”
Section: Water Quality Parameter Evaluationmentioning
confidence: 99%
“…It is also comparable to the permeate water obtained from conventional seawater desalination by reverse osmosis (SWRO). 48 The comparative performances (Table S2 †) suggest that the NRIO-20 composite sponge has the potential for use as a solar evaporator for the production of clean water.…”
Section: Solar-driven Clean Water Productionmentioning
confidence: 99%